1981
DOI: 10.1007/bf00238808
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between input and output of cells in motor and somatosensory cortices of the chronic awake rat

Abstract: Experiments using the same glass microelectrode (6--8 M omega) for recording and stimulating were performed on 12 rats in which 379 cortical cells were studied in 65 penetrations through the motor and somatosensory cortical zones. To avoid anaesthetic effects the rats were chronically implanted with a head system derived from the one developed by Noda et al. (1971). These animals well accepted head fixation and the peripheral receptive fields could thus be easily investigated. In a preliminary experiment the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
29
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 12 publications
10
29
0
Order By: Relevance
“…Similarly, Malis et al (1953) found that sensory-evoked potentials could be elicited in precentral motor cortex in monkeys. More recent electrophysiological studies have confirmed somatic motor functions in S1 (Doetsch and Gardner, 1972;Sapienza et al, 1981;Gioanni and Lamarche, 1985) and somatic sensory functions in M1 (Welt et al, 1967;Thompson et al, 1970;Rosén and Asanuma, 1972;Wiesendanger, 1973;Asanuma et al, 1979Asanuma et al, , 1980Tanji and Wise, 1981;Strick and Preston, 1982;Asanuma and Arissian, 1984;Nudo et al, 1997).…”
Section: Motor Representationmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, Malis et al (1953) found that sensory-evoked potentials could be elicited in precentral motor cortex in monkeys. More recent electrophysiological studies have confirmed somatic motor functions in S1 (Doetsch and Gardner, 1972;Sapienza et al, 1981;Gioanni and Lamarche, 1985) and somatic sensory functions in M1 (Welt et al, 1967;Thompson et al, 1970;Rosén and Asanuma, 1972;Wiesendanger, 1973;Asanuma et al, 1979Asanuma et al, , 1980Tanji and Wise, 1981;Strick and Preston, 1982;Asanuma and Arissian, 1984;Nudo et al, 1997).…”
Section: Motor Representationmentioning
confidence: 81%
“…Cortical sites receiving tactile input from particular parts of the face, hand, or trunk in monkeys roughly overlap sites that result in movements in closely related parts of the body upon stimulation (Woolsey, 1958;Doetsch and Gardner, 1972). A similar rough congruence of sensory input and motor output is seen in sensorimotor cortex of rats (Sapienza et al, 1981) cats (Asanuma et al, 1968), and primates (Rosén and Asanuma, 1972;Sessle and Weisendanger, 1982;Strick and Preston, 1982). Stimulating sites that evoked movement of vibrissae generally overlapped sites that were responsive to stimulation of the vibrissae, lower jaw, face, and snout.…”
Section: Motor Representationmentioning
confidence: 88%
“…These ICMS studies, along with investigations using single-neuron recordings, reversible cold block, or lesioning techniques, have underscored the crucial role of the face-M1 in the generation and control of orofacial motor functions (e.g., jaw opening, tongue protrusion, whisking, and mastication; for review see Ebner, 2005;Sessle et al, 2005Sessle et al, , 2007. Furthermore, it has been revealed that face-M1 receives somatosensory inputs from the orofacial region, including the teeth Miyashita et al, 1994;Murray et al, 2001;Sapienza et al, 1981), to further assist in the generation and control of orofacial motor functions (Haas and Lennon, 1995;Hiraba et al, 2007;Inoue et al, 1989;Johansson et al, 2006;Murray et al, 2001;Yao et al, 2002).…”
mentioning
confidence: 96%
“…Neuroplastic changes can be induced within face-S1 somatosensory representations by manipulations of orofacial somatosensory inputs (Ebner, 2005;Henry et al, 2005). Although jaw and tongue movements can be evoked by ICMS applied to face-S1 and disruption of this region can severely impair orofacial motor behaviors Castro, 1975;Hiraba et al, 2007;Murray et al, 2001;Neafsey et al, 1986;Sapienza et al, 1981), no study has examined whether tooth loss induces neuroplasticity in the ICMS-defined features of face-S1.…”
mentioning
confidence: 97%
See 1 more Smart Citation